Odsev pravnega položaja in življenjskih razmer žensk v slovenskih ljudskih družinskih baladah - Golež Kaučič, Marjetka (Etnolog. Nova vrsta (Ljubljana), 2001)
The paper researches the individual and typical phenomena of women's legal status and their material, social and emotional living conditions as reflected in individual Slovene popular family ballads. The author's primary focus is on the relationships and the roles woman had in the family (daughter, bride, daughter-in-law, mother-in-law, wife, mother, sister, child murderess), derivin from the individual family relationships in the past, and she establishes the changes of women's status in the course of time. In addition to the above mentioned aspects teh author includes completely new one when she researches the connections between women as the subjects of folk songs and women as their carriers (and performers)
Keywords: woman; ženske; Ethnopoetics; ljudske pesmi; balade; folkloristics; folkloristika; tekstna lingvistika; Slovenia; Slovenija